Pengaruh Viral Marketing, Online Customer Review, Dan Online Customer Rating Terhadap Keputusan Pembelian Pada Tik Tok Shop - Chasanah, Nurul Radhiatul; Asiyah, Siti; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to test and analyze the influence of viral marketing, online customer reviews, and online customer ratings on purchasing decisions in social commerce tik tok shop (Case study on Cosrx buyer decisions in Malang City). The type of research used in this study is a survey with a quantitative approach. The population in this study were Cosrx buyers in Tik Tok shop in Malang City. In this study, the sampling method follows the formula suggested by Malhotra with calculations showing that the number of samples required is 16 × 5 is 80 respondents. The results of the study indicate that there is a simultaneous influence between the variables of viral marketing, online customer reviews, and online customer ratings on purchasing decisions. The viral marketing variable influences purchasing decisions. The online customer review variable influences purchasing decisions. The online customer rating variable does not influence purchasing decisions. Keywords : The Influence Of Viral Marketing, Online Customer Reviews, Online Customer Ratings And Purchasing Decisions